Physical Cues of Matrices Reeducate Nerve Cells - Luo, Yiqian; Li, Jie; Li, Baoqin; Xia, Yuanliang; Wang, Hengyi; Fu, Changfeng (Frontiers in Cell and Developmental Biology, 2021)
The behavior of nerve cells plays a crucial role in nerve regeneration. The mechanical, topographical, and electrical microenvironment surrounding nerve cells can activate cellular signaling pathways of mechanical transduction to affect the behavior of nerve cells. Recently, biological scaffolds with various physical properties have been developed as extracellular matrix to regulate the behavior conversion of nerve cell, such as neuronal neurite growth and directional differentiation of neural stem cells, providing a robust driving force for nerve regeneration. This review mainly focused on the biological basis of nerve cells in mechanical transduction. In addition, we also highlighted the effect of the physical cues, including stiffness, mechanical tension, two-dimensional terrain, and electrical conductivity, on neurite outgrowth and differentiation of neural stem cells and predicted their potential application in clinical nerve tissue engineering.